Presupuesto de la región Loreto y su relación con el presupuesto nacional de la división funcional 046 deportes periodo 2018 – 2022 - Murrieta Pizango, Hugo Orlando (2024)
Sport, as a public policy, is essential for its ability to promote health and well being, personal development, social integration, the reduction of crime and violence, and the economic impact. The general objective of this study is to determine the relationship between the budget at the level of the Loreto region and the budget at the national level of the functional division 046 Sports in the period 2018 - 2022, for this a non-experimental design at a correlational level was addressed and the budget data at the level of the Loreto region and the national total oriented to sport, identifying that the data analysis reveals a marked variability in the amounts allocated and executed for sport throughout the years studied, both at the regional level in Loreto and at the national level, indicating fluctuations in investment in this area, despite the fact that the budget allocation for sports in Loreto represents only a minimal fraction of the national budget, no clear relationship is observed between the allocation of funds at the regional and national level, furthermore, no correlation is found between the execution of the funds assigned and executed both at the regional and national level, neither in terms of the specific functional division nor in the economic classification, during the period analyzed from 2018 to 2022 and concluding that there is no relationship between the budget at the of the Loreto region and the national budget of the functional division 046 Sports in the period 2018 – 2022.